In my father's house. C. G. Jung's "Memories, Dreams, Reflections:" A son in search of father. - Wright, Robert S. G. (University of Ottawa (Canada), 1999)
This thesis examines Carl Jung's autobiography, Memories, Dreams, Reflections. Within this text the reader is provided with rich and profound insights into the life of Carl Gustav Jung. This document sheds enormous light on the personality of one of this century's most important figures in the world of psychology and religion. For a generation after Jung's death, scholars have depended almost exclusively on Memories, Dreams, Reflections for their biographical facts about Jung. This text is invaluable for data about his early childhood, and vital for the description of the catastrophic break with Freud. While the autobiography is a summary of the whole of Jung's life, this work examines that life with an eye to the early years in the vicarage. The writer has a special interest in exploring Jung's relationship to his father, the Reverend Paul Jung, a kinship not only vital and revealing but to this point in time, a relationship which has been largely ignored. To date there has been little data available on the Reverend Paul Jung, and even less research on his influence upon his son, Carl. Within this dissertation the reader will discover new information, fresh insights into Jung's father and his lasting influence upon his quite remarkable son. (Abstract shortened by UMI.)
Keywords: Biography.